Simulasi Pengaruh Angin Pada Bangunan Di Kalimantan Selatan Menggunakan Software Thunderhead Pyrosim: Simulation Of Wind Effects On Buildings In South Kalimantan Using Thunderhead Pyrosim Software - Tjitradi, Darmansyah; Eliatun, Eliatun; Barkiah, Ida; Karim, Abdul; Prasetia, Irfan; Lestari, Della Dwi; Tjitradi, Aeron (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
South Kalimantan has a tropical climate with high rainfall and high humidity. The weather in this area can also change rapidly, with strong winds and heavy rain, potentially damaging buildings and infrastructure. In recent decades, there have been significant improvements in building design and construction, especially in terms of strength and safety. However, many buildings are still vulnerable to wind damage, especially in areas prone to storms or strong winds. This research aims to simulate the effect of wind on a simple residential building in South Kalimantan measuring 6.0 m x 6.0 m, with varying roof slope angles of 15, 30, 35, and 40 degrees, using Thunderhead Pyrosim Software Version 6.9.1 (Academic License).. Based on the results of this study, it can be known that according to online BMKG data, the maximum wind speed that occurs in South Kalimantan is 21 m/det, and based on the results of software simulation, it can be known that the greater the slope angle of the roof, the greater the Cd (drag coefficient) / resistance of the building, which means that the building will have a higher possibility of being carried away by the wind. Conversely, a lower drag coefficient value indicates that the roof will be more resistant to wind flow pressure, or in other words, more aerodynamic, so that houses in windy areas can use roofs with a small slope angle (15o - 35o ) or concave roofs for better aerodynamics, and provide a barrier in the direction of the wind.